Advanced oxidation protein products play critical roles in liver diseases. (20th March 2019) - Zhao, Yalei; Zhang, Lingjian; Ouyang, Xiaoxi; Jiang, Zhengyi; Xie, Zhongyang; Fan, Linxiao; Zhu, Danhua; Li, Lanjuan
Abstract: There is a complex oxidant and antioxidant system that maintains the redox homoeostasis in the liver. While suffering from exogenous or endogenous risk factors, the balance between oxidants and antioxidants is disturbed and excessive reactive oxygen species are generated, resulting in oxidative stress. Oxidative stress is prevalent in various liver diseases and is thought to be involved in their pathophysiology. Advanced oxidation protein products are generated under conditions of oxidative damage and are newly described protein markers of oxidative stress. Previous studies have underscored the universal pathogenic roles of oxidation protein products in various diseases. However, investigations into how these products participate in the development of liver diseases have been superficial and insufficient. In this review, we highlight the current understanding of the roles of advanced oxidation protein products in liver disease pathogenesis and the underlying mechanisms. Moreover, we summarize the current studies on advanced oxidation protein products in infectious and noninfectious, acute and chronic liver diseases. Different strategies for targeting these advanced oxidation protein products and future perspectives, which may pave the way for developing new therapeutic strategies, will also be discussed here.